Removal of LIF (leukemia inhibitory factor) results in increased vitamin A (retinol) metabolism to 4-oxoretinol in embryonic stem cells - Lane, Michelle A. (The National Academy of Sciences, 1999)
Retinoids, vitamin A (retinol) and its metabolic derivatives, are required for normal vertebrate development. In murine embryonic stem (ES) cells, which remain undifferentiated when cultured in the presence of LIF (leukemia inhibitory factor), little metabolism of exogenously added retinol takes place. After LIF removal, ES cells metabolize exogenously added retinol to 4-hydroxyretinol and 4-oxoretinol and concomitantly differentiate. The conversion of retinol to 4-oxoretinol is a high-capacity reaction because most of the exogenous retinol is metabolized rapidly, even when cells are exposed to physiological (≈1 μM) concentrations of retinol in the medium. No retinoic acid or 4-oxoRA synthesis from retinol was detected in ES cells cultured with or without LIF. The cytochrome P450 enzyme CYP26 (retinoic acid hydroxylase) is responsible for the metabolism of retinol to 4-oxoretinol, and CYP26 mRNA is greatly induced (>15-fold) after LIF removal. Concomitant with the expression of CYP26, differentiating ES cells grown in the absence of LIF activate the expression of the differentiation marker gene FGF-5 whereas the expression of the stem cell marker gene FGF-4 decreases. The strong correlation between the production of polar metabolites of retinol and the differentiation of ES cells upon removal of LIF suggests that one important action of LIF in these cells is to prevent retinol metabolism to biologically active, polar metabolites such as 4-oxoretinol.